LITTing up Gliomas—Is the Future Bright? - Philip J. O’Halloran; Jack Henry; Michael Amoo; Aristotelis Kalyvas; Nilesh Mohan; Gelareh Zadeh; Suneil K. Kalia; Paul N. Kongkham (World Neurosurgery: X, 2023)
Background: Laser interstitial thermal therapy (LITT) represents an attractive therapeutic strategy for several intracranial pathologies; however, there is a paucity of literature regarding its efficacy for the treatment of gliomas. Methods: MEDLINE, EMBASE, Scopus, and Web of Science were searched from inception until March 19, 2021. Studies specifically relating to the use of LITT in treatment of glioma were eligible for inclusion. A meta-analysis of means was performed to assess the progression-free survival (PFS) and overall survival (OS) following LITT and descriptive statistics relating to patients undergoing LITT were collated and a meta-analysis of proportions was also performed to assess the rate of complications. Results: In total, 17 studies were included for the meta-analysis, comprising 401 patients with 408 gliomas of which 88 of 306 (28.8%) were grade 1 or 2 and 218 of 306 (71.2%) were grade 3 or 4. Of these, 256 of 408 (62.8%) were primary presentation and 152 of 408 (37.2%) were recurrent. The pooled mean OS was 13.58 months (95% confidence interval [CI] 9.77–17.39) and the PFS was 4.96 months (95% CI 4.19–5.72). The OS and PFS of recurrent glioblastoma were 12.4 months (95% CI 9.61–16.18) and 4.84 months (95% CI 0.23–9.45), respectively. Complications occurred in 114 of 411 (24%; 95% CI 14–41), of which 44 (11%) were transient deficits. Conclusions: There is an increasing body of evidence demonstrating the use of LITT in the surgical management of deep-seated gliomas in patients of poor performance status. However, further studies are required to interrogate the clinical effectiveness of LITT in the setting of gliomas as well as assessing the survival benefit versus standard treatment alone.